Peran Kepemimpinan, Motivasi, dan Kepuasan Kerja dalam Meningkatkan Kinerja Karyawan - Nurul Maghfiroh; Anis Turmudhi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the influence of leadership, motivation, and job satisfaction on employee performance at CV Adelindo Abadi in Semarang City. The background of this research is based on the importance of human resources as a key factor in achieving organizational goals. Employee performance is not only determined by technical skills but is also strongly influenced by the quality of leadership implemented by management, the level of motivation experienced by employees, and the extent of job satisfaction that creates a supportive work environment. These three aspects are believed to play an essential role in enhancing productivity and strengthening the company’s competitiveness. The research method applied is quantitative with a descriptive approach. Data were collected through questionnaires distributed to employees who served as respondents. The data were then analyzed using multiple linear regression to examine the influence of leadership, motivation, and job satisfaction, both partially and simultaneously, on employee performance. The findings of this study indicate that leadership, motivation, and job satisfaction have a positive and significant effect on employee performance, whether tested simultaneously or individually. This means that the better the leadership practices, the higher the motivation provided, and the greater the level of job satisfaction experienced by employees, the more optimal their performance will be. Based on these results, it is recommended that company management consistently develop effective leadership styles, provide motivation that is aligned with employee needs, and establish a comfortable and supportive work environment. By doing so, the company can continuously improve employee performance and remain competitive in an increasingly dynamic business environment.